Towards real-world biomechanical detection of fatigue, energy, and injury in runners using Wearable Trunk Accelerometry - Schutte, Kurt (Stellenbosch : Stellenbosch University, 2018)
Thesis PhD (Sport Sc)--Stellenbosch University, 2018.